2017
DOI: 10.1093/ofid/ofx216
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Enterobacteriaceae Infections in Patients on Renal Replacement Therapy

Abstract: Background Patients on chronic intermittent renal replacement therapy (RRT) are at risk for infection with carbapenem-resistant Enterobacteriaceae (CRE). However, the impact of RRT on outcomes after CRE infections remains to be defined. Here we perform a comparison of outcomes for CRE-infected patients with preserved renal function compared with CRE-infected patients on RRT. Methods Cases and controls were defined from a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Other meta-analyses also demonstrated significant positive associations between CRE and mortality when CSE-infected patients were used as a baseline. [6][7][8] We also revealed the association between the primary outcomes and these factors including CCI score, 9,11,16,29 number of days with an invasive device or indwelling line, 13,15,21 septic shock, 30,31 acute respiratory failure, 13 site of severe infection, 13,32 and moderate to severe renal impairment 33,34 ; such associations were well supported by multiple studies. 10,35 For the secondary outcomes, we found that a 90-day readmission rate was associated with CRE infections, agreeing with a study by Zilberberg et al 22 In addition, the mean of LOS and the cost of treatment in the CRE-infected patients were considerably higher than those in the CSE-infected patients, which agrees with several other studies.…”
Section: Discussionsupporting
confidence: 68%
“…Other meta-analyses also demonstrated significant positive associations between CRE and mortality when CSE-infected patients were used as a baseline. [6][7][8] We also revealed the association between the primary outcomes and these factors including CCI score, 9,11,16,29 number of days with an invasive device or indwelling line, 13,15,21 septic shock, 30,31 acute respiratory failure, 13 site of severe infection, 13,32 and moderate to severe renal impairment 33,34 ; such associations were well supported by multiple studies. 10,35 For the secondary outcomes, we found that a 90-day readmission rate was associated with CRE infections, agreeing with a study by Zilberberg et al 22 In addition, the mean of LOS and the cost of treatment in the CRE-infected patients were considerably higher than those in the CSE-infected patients, which agrees with several other studies.…”
Section: Discussionsupporting
confidence: 68%
“…(ESBL)-producing and CR Enterobacterales demonstrate that approximately 20% of patients require RRT at baseline and that the need for RRT is independently associated with clinical failure, development of resistance, and mortality [8][9][10][11][12]. Although mortality in this population is likely multifactorial in etiology, pharmacokinetic (PK) alterations in patients receiving continuous RRT (CRRT) have been shown to lead to suboptimal antimicrobial exposures and worse clinical outcomes, especially for highly renally eliminated agents with time-dependent pharmacodynamic (PD) properties such as the β-lactams [13].…”
Section: Key Pointsmentioning
confidence: 99%
“…13 , 14 There are scant data other than the above studies for mortality of carbapenem-resistant Enterobacteriaceae (CRE) in haemodialysis patients. Eilertson et al 25 reported higher mortality with CRE infections in patients on renal replacement therapy, although only one-quarter of patients had bacteraemia and the median age was 62 years. We did not see a different or higher mortality rate for CRE bacteraemia in our cohort comprising mainly haemodialysis patients, due in part to the younger median age and prompt source control.…”
Section: Discussionmentioning
confidence: 99%